O direcionamento publicitário na Internet e suas principais implicações jurídicas - Arantes, Carla Cavalheiro (2018)
This paper aims at exposing the concept and functioning of behavioral advertising on Internet, its main legal implications and the parameters that must be observed by suppliers to ensure the lawfulness of said practice. This paper will show that for the advertising to be directed to a certain consumption’s profile, consumer data must be collected and used by suppliers. As the behavioral advertising on Internet has to use personal data and deal with technological mechanisms, which, in many cases, are not properly informed to consumers, it may violate their rights to privacy and information. The purpose of this paper, however, is to rule out extreme opinions that consider behavioral advertising and the way data is collected for this intent unlawful, as well as to present a legal solution that respect consumers’ rights to privacy and information, and concurrently, allow the practice of behavioral advertising on Internet